Suppressive effects of dRYamides on feeding behavior of the blowfly, Phormia regina. Issue 1 (December 2015) - Maeda, Toru; Nakamura, Yuki; Shiotani, Hajime; Hojo, Masaru; Yoshii, Taishi; Ida, Takanori; Sato, Takahiro; Yoshida, Morikatsu; Miyazato, Mikiya; Kojima, Masayasu; Ozaki, Mamiko
Abstract Recently, dRYamides-1 and -2 have been identified as ligands of the neuropeptide Y-like receptor CG5811 inDrosophila melanogaster . It has also been reported in brief that injection of dRYamide-1suppresses the early feeding behavior called proboscis extension reflex (PER) in the blowflyPhormia regina . Immunohistochemical analyses by our group using anti-dRYamide-1 antiserum indicated symmetrical localization of 32 immunoreactive cells in the brain ofP. regina . In order to analyze the mechanism of feeding regulation, we further investigated the effects of dRYamide-1 and -2 on intake volume, PER exhibition, and activity of the sugar receptor neuron. After injection of dRYamide-1 or -2, flies showed little change in the intake volume of sucrose solution, but a significant depression of PER to sucrose. Injection of dRYamide-1 revealed a significant decrease in the responsiveness of the sugar receptor neuron, although the injection of dRYamide-2 did not. These results suggest that the dRYamide peptides decrease feeding motivation in flies, as evaluated by PER threshold, through a mechanism that partially involves desensitization of the sugar receptor neuron.